THE INTEGRATION OF GENRE BASED APPROACH INTO SCIENTIFIC APPROACH IN WHEN ENGLISH RINGS A BELL TO TEACH RECOUNT TEXT - Amalia, Rizky Nurul; Hartono, Rudi (Language Circle: Journal of Language and Literature, 2015)
This study analyzed the integration of Genre-based Approach into the Scientific Approach elements as they are represented in a textbook entitled When English Rings a Bell published by the Ministry of Education and Culture, Indonesia. This study used descriptive qualitative method to analyze the integration of two approaches in the textbook. The result showed that there were four sections of integrations. The first was the integration of BkoF into Observing and Questioning in Scientific Approach. The second was the integration of Modeling of Text (MoT) into Observing, Questioning, and Collecting Information. The third was the integration of Joint Construction of Text (JCoT) into Collecting Information and Associating. The last is the integration of Individual Construction of Text (ICoT) into Communicating. Based on those findings, Genre Based Approach was represented in Scientific Approach; all of the principles consisted in Genre-based Approach were accommodated in Scientific Approach.